2020
DOI: 10.1186/s12944-020-01247-1
|View full text |Cite
|
Sign up to set email alerts
|

Trans fatty acid intake among Chinese population: a longitudinal study from 1991 to 2011

Abstract: Objective: This study was aimed to roughly describe individual Trans Fatty Acids (TFAs) intake and the percentage of energy intake(E%), and identify major food sources in the Chinese population, taking gender, age, and regional distribution into the consideration, as well as examining temporal changes over the course of 20 years. Method: This multi-center study, covering nine provinces among populations aged ≥ 3 in China, was conducted to collect food consumption information from 1991 to 2011. A classical asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 26 publications
4
8
1
Order By: Relevance
“…As in our investigation, many other studies have reported higher consumption of trans fats among younger persons (62,63,65) . The intake of trans fats has been increasing rapidly during the last years (62,65) , despite their well-known harmful effects on CVD and mortality (66) . Different factors may explain this phenomenon in underage individuals: first, there is a positive correlation between ingestion of trans fats or sugar-sweetened beverages and time spent watching television (67) .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…As in our investigation, many other studies have reported higher consumption of trans fats among younger persons (62,63,65) . The intake of trans fats has been increasing rapidly during the last years (62,65) , despite their well-known harmful effects on CVD and mortality (66) . Different factors may explain this phenomenon in underage individuals: first, there is a positive correlation between ingestion of trans fats or sugar-sweetened beverages and time spent watching television (67) .…”
Section: Discussionsupporting
confidence: 86%
“…Concerning trans fats, the influence of US culture and habits about practical and cheap foods may be greater in higher income groups (63) . As in our investigation, many other studies have reported higher consumption of trans fats among younger persons (62,63,65) . The intake of trans fats has been increasing rapidly during the last years (62,65) , despite their well-known harmful effects on CVD and mortality (66) .…”
Section: Discussionsupporting
confidence: 86%
“…For example, information on trans-fat intake was not included in the study. However, there is a very low intake of trans-fat in the Chinese population (44) , and our findings were less likely to be influenced by the lack of trans-fatty acid intake. Third, Accepted manuscript this is an observational study, thus the causality of the observed associations cannot be inferred.…”
Section: Discussionmentioning
confidence: 45%
“…This study did not identify foods that remarkably contribute to TFA intake. However, even with foods that contribute equally to TFA intake, their ranking may vary depending on the country's dietary background (12,13,55) .…”
Section: Discussionmentioning
confidence: 99%